Piano sonata no. 16 in G major, op. 31, no. 1, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Germany; Eduard Hallberger; Stuttgart, 2024)
Mid-nineteenth century edition of the Piano Sonata no. 16 in B-flat major, op. 31, no. 1, edited by Ignaz Moscheles and published by Eduard Hallberger in Stuttgart as no. 16 of the series "L. v. Beethoven's sämmtliche Sonaten für Pianoforte."